Impact of Stimulation on Infant’s Communication Development in Kuantan, Indonesia; A 2- 4- and 6-Month Follow-up Study (Indian Journal of Public Health Research & Development, 2020)
Introduction: Stimulation has a large effect on children’s development, but the impact of stimulationespecially in infant’s communication development was unknown. The primary objective of the study wasto evaluate the effect of stimulation on infant’s communication development at 2, 4 and 6 months of age.Method: This is a longitudinal study held in Kuantan Singingi District, Riau Province-Indonesia fromJanuary to October 2017. We enrolled all newborns whose parents lived and settled in Kuantan Singingidistrict and had normal delivery. Newborn with major congenital abnormalities, pathological jaundice, lowbirth weight and whose mother were smoking were excluded. Data of infant’s communication developmentand parent’s stimulation were collected at 2, 4 and 6 months. the Age and Stages Questionnaire thirdedition (ASQ-3) was administered to assess infant’s communication development and the Infant/toddlerHome Observation for Measurement of the Environment (HOME) Inventory was administered to assessparent’s stimulation. We analyzed the relationship between parent’s stimulation and infant’s communicationdevelopment at 2, 4 and 6 months using logistic regression analysis.Results: We enrolled 474 newborns and their parents. Compared to less stimulated infants, infants who gotenough stimulation by their parents had better communication developments at 2 months (OR 11.1 95% CI:3.8-32.4), 4 months (OR 2.6 95% CI: 1.3-5.3) and 6 months (OR: 2.2 95% CI 1.1-4.3).Conclusion: Giving enough stimulation by parents can affect the communication developments of theirinfants.
Keywords: 2-6 months; stimulation; infants; communication development